PENGARUH KOMISARIS INDEPENDEN, KOMITE AUDIT, INDEPENDENSI, DAN SPESIALISASI INDUSTRI AUDITOR TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2015) - Elisabeth Veronika Sipahutar; Amir Hasan; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to determine the influence of independent commissioners, audit committee, independence, and auditor industry specialization on the integrity of the financial report. Independent variables used in this study are independent commissioners, audit committee, independence, and auditor industry specialization, while the dependent variable is the integrity of financial report that is measured by using conservatism index. Population used in this study is mining companies listed on Indonesia Stock Exchange period among 2011-2015. Sample was collected by purposive sampling method. Total 14 mining companies were taken as study’s sample. This study used secondary data collected through Indonesia Stock Exchange (www.idx.co.id). The research data were analyzed with multiple linear regression model with help of SPSS software version 21,0. The results of this research showed that independent commissioner, independence, and auditor industry specialization had significant effect to the integrity of financial report. Meanwhile, audit committee had not significant effect to the integrity of financial report.Keywords: Independent Commissioners, Audit Committee, Independence, Auditor Industry Specialization, Integrity of Financial Report